Modules and their endomorphism rings. (October 2019) - Susanto, H; Irawati, S; Hidayah, I N; Irawati,
Abstract: Let R and S be a pair of equivalent rings. We will prove that if R has property that a pair of modules over R are isomorphic if and only if their endomorphism rings are isomorphic than S has same property, i.e. a pair of modules over S are isomorphic if and only if their endomorphism rings are isomorphic.